Epigenetic and genetic events of oral squamous cell carcinoma: perspective on DNA methylation, silencing of tumor suppressor gene, and activating oncogenes: Genetic and epigenetic changes in oral cancer - Nizar Jawad, Zainab (Cellular and Molecular Biology, 2025)
Oral squamous cell carcinoma (OSCC) is a major health burden in most parts of the world, and pathogenesis of the disease is strongly associated with a complex combination between genetic mutations and epigenetic alterations. The current study will explore the DNA methylation phenomenon and how it affects the silencing of tumour suppressor genes and activate oncogenes in OSCC in a bid to explain the driving molecular process behind tumour development. We evaluated 50 samples of the OSCC tissues with 50 of the adjacent normal tissues, evaluated DNA methylation patterns with methylation-specific PCR and quantitative reverse-transcriptase PCR measured the expression of the DNA repair genes like BRCA1 and MLH1, among others. This finding showed different levels of DNA methylation of cancerous and normal tissues with hypermethylation causing the inactivation of important tumor suppressor genes and hypomethylation causing the activation of oncogenes. In addition, the downregulation of DNA repair genes was noted to be highly significant in OSCC samples indicating that genomic-instability may be related to epigenetic changes. These results demonstrate that aberrant DNA methylation is central to OSCC growth and progression, thus helping in the future use of methylation patterns that can be used as early detection, diagnosis, and prognostic biomarkers. Our findings support the idea that genetic, along with epigenetic, profiling is an issue of key importance toward comprehending OSCC biology and personalized therapeutic interventions. It is recommended that further confirmation be carried out to verify the clinical significance of such epigenetic markers in bigger cohorts, as well as testing such markers in guided therapies, which might eventually lead to better patient outcomes in the management of oral cancer.